Introducing ethics - Robinson, Dave (Icon Books, 1996)
Ethics has become the burning issue of current moral philosophical thought, raising the spectre of responsibility at a time when responsibility seems entirely replaced by uncertainty and relativism. What is the place of individual choice and consequence in a post-Holocaust world of continuing genocidal ethnic cleansing? Is 'identity' now a last-ditch cultural defence of ethic nationalisms and competing fundamentalisms? In a climate of instant information, free markets and possible ecological disaster, how do we define 'rights', self-interest and civic duties? What are the acceptable limits of scientific investigation and genetic engineering, the rights and wrongs of animal rights, euthanasia and civil disobedience? This book confronts these dilemmas, tracing the arguments of the great moral thinkers, including Socrates, Plato, Aristotle, Hobbes and Kant, and brings us up to date with postmodern critics.